2009
DOI: 10.1080/08958370802687493
|View full text |Cite
|
Sign up to set email alerts
|

An effort to test the embryotoxicity of benzene, toluene, xylene, and formaldehyde to murine embryonic stem cells using airborne exposure technique

Abstract: Benzene, toluene, xylene, and formaldehyde are well-known indoor air pollutants, especially after house decoration. They are also common pollutants in the working places of the plastic industry, chemical industry, and leather industry. It has been reported that these pollutants cause people to be irritated, sick, experience a headache, and be dizzy. They also have the potential to induce asthma, aplastic anemia, and leukemia, even cause abortion or fetus malformation in humans. In this study, the airborne toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In humans, increased Th2 polarisation of neonatal immune responses has been associated with maternal VOC exposure during pregnancy [82]. Although little evidence exists suggesting that VOCs influence lung growth, embryotoxic effects from exposure to airborne VOCs on murine embryonic stem cells have been reported [83], and adverse effects on rat embryo/fetal development have been linked to VOC release from their cages [84].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, increased Th2 polarisation of neonatal immune responses has been associated with maternal VOC exposure during pregnancy [82]. Although little evidence exists suggesting that VOCs influence lung growth, embryotoxic effects from exposure to airborne VOCs on murine embryonic stem cells have been reported [83], and adverse effects on rat embryo/fetal development have been linked to VOC release from their cages [84].…”
Section: Discussionmentioning
confidence: 99%
“…High exposure to xylene may be observed in histopathological laboratory technicians especially during the deparaffinization of tissue sections [ 3 ]. The organ systems that are most susceptible to xylene are the lungs, skin, central nervous system, liver, and kidneys [ 4 ]. Many studies have also shown adverse effects of xylene on human and animal reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Previous studies have found that HCHO and BTX exposure has negative effects on the reproductive, immune, cardiovascular and respiratory, and can cause blood system disorders and leukaemia. [32][33][34][35][36][37] Researchers found that different genders and age groups have different sensitivity to pollutants. 38,39 A number of studies have shown that refurnished residences can cause rhinitis, eyes and skin diseases, asthma and leukaemia, especially in children and women.…”
Section: Introductionmentioning
confidence: 99%